What and how long does it take to get tenure? The case of economics and business administration in Austria, Germany and Switzerland - Günther G. Schulze; Susanne Warning; Christian Wiermann (University of Freiburg, Department of International Economic Policy (iep), 2008)
This paper investigates the determinants of tenure decisions in Germany, Austria and the German-speaking part of Switzerland for professorships in economics, business administration and related fields. Our data set comprises candidates who were awarded tenure as well as those who were eligible but were not tenured. We show that business candidates have a higher probability of being tenured than economists. Youth, marital status, and publications matter; gender and children do not. The market for first appointments in economics relies much more on publication performance than the market for business administration.
Keywords: A11; I23; 330; habilitation; tenure; academic labor market